PERAN GURU DALAM MENINGKATKAN MUTU PESERTA DIDIK DI SD DARUL HIKAM BANDUNG DI ERA 4.0 - Barirotut Taqiyah; Lukluil Maknun; Faiqotul Mamluah; Fiki Aufiya; Elya Umi Hanik (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The government has made various efforts to produce superior seeds as candidates for the nation's successor. One of the efforts made is to improve the quality of education which can be seen from the role of teachers, processes in learning, students and the applicable curriculum. In era 4.0 the role of educators in improving the quality of education, especially in improving the quality of students is very important. The purpose of this fieldwork course is to find out how to standardize education, especially in the process of improving the quality of students at SD IT Darul Hikam Bandung. The method used in this activity is a qualitative method. The results of this study are SD IT Darul Hikam has implemented several separate criteria to recruit students to be. The learning process at SD IT Darul Hikam has implemented the 2013 curriculum so that students do many experiments that make students active and develop. This improving the quality of students can be realized